THE CORRELATION BETWEEN STUDENTS’ FAMILY SUPPORT AND ENGLISH LEARNING ACHIEVEMENT OF THE THIRD-YEAR STUDENTS AT THE ENGLISH STUDY PROGRAM OF UNIVERSITAS RIAU - Aldo Irsyaf Putra; Novitri; Erni; Zaldi Harfal (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This correlation research aimed to examine the relationship between students’ family support and English learning achievement of third-year students in the English study program at Universitas Riau. The instruments included a 34-item family support questionnaire, adapted from the Social Family Support Scale (Thoriq, 2013), and students’ English learning achievement scores obtained from their GPA in English language skills subjects: Listening Comprehension 1–3, Speaking 1–3, Reading Comprehension 1–3, and Writing 1–3. The population consisted of 110 third-semester students, with 89 students selected using cluster random sampling. The results indicated a moderate correlation between family support and English learning achievement. Students’ family support was at a high level, and their English learning achievement was at a good level (B+), with family support contributing 16.9% to students’ achievement.